PERLINDUNGAN HUKUM KEPADA PEMBELI YANG BERITIKAD BAIK DALAM HAL DILAKUKANNYA PENCATATAN BLOKIR DAN SITA PADA SERTIPIKAT HAK ATAS TANAH OLEH KANTOR PERTANAHAN KOTA MEDAN - CAHRYA HALOHO (PREMISE LAW JURNAL, 2015)
Land registration, required by the government and in line with Article 19 of UUPA, is aimed to guarantee legal certainty on land rights by the issuance of land rights certificates. The legal problems arises when the action of suspension and confiscation registration done by an applicant is not correct because at the time of the registration the certificate is not in the name of the real owner, or the certificate has been transferred to another party (good faith buyer). The result of the research showed that the registration procedure of suspension and confiscation on land rights certificates at the Land Office had to fulfill the requirement of suspension and confiscation stipulated by the Regulation of the Head of BPN (National Land Board) No. 1/2010 on Service Standard and Regulation on Land. Some factors which cause the case of the registration of suspension and confiscation are legal provisions which implies that there is no fixed regulation about legal protection for good faith buyers, and law enforcements that are directly related to the process of legal enforcement are District Court and the National Land Board of the Land Office which plays an important role in conducting the registration of suspension and confiscation. In this case, the judge who stipulates the Verdict of Foreclosure ignores the legal protection for good faith buyers and the Land Office pays attention only to their own interest or to parties concerned in carrying out the registration of suspension and confiscation. Keywords:   Legal Protection, Good Faith Buyers, Suspension and Confiscation Certificate